2019
DOI: 10.1038/s41419-019-1653-7
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic flux disruption contributes to Ganoderma lucidum polysaccharide-induced apoptosis in human colorectal cancer cells via MAPK/ERK activation

Abstract: Targeting autophagy may serve as a promising strategy for cancer therapy. Ganoderma lucidum polysaccharide (GLP) has been shown to exert promising anti-cancer effects. However, the underlying mechanisms remain elusive. Whether GLP regulates autophagy in cancer has never been reported. In this study, GLP induced the initiation of autophagy in colorectal cancer (CRC) HT-29 and HCT116 cells, as evidenced by enhanced level of LC3-II protein, GFP-LC3 puncta, and increased formation of double membrane vacuoles. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 73 publications
3
62
0
3
Order By: Relevance
“…During the process of autophagosome-to-autolysosome formation, the Beclin 1 complex and ERK1/2 serve an important role in regulating autophagy (38). The results of the present study indicated an increase in LC3-II and a decrease in p62 content following HYSA treatment of Hep-G2 cells, suggesting an induction of autophagy.…”
Section: Discussionsupporting
confidence: 54%
“…During the process of autophagosome-to-autolysosome formation, the Beclin 1 complex and ERK1/2 serve an important role in regulating autophagy (38). The results of the present study indicated an increase in LC3-II and a decrease in p62 content following HYSA treatment of Hep-G2 cells, suggesting an induction of autophagy.…”
Section: Discussionsupporting
confidence: 54%
“…MAPK signaling pathway plays a role in many systems of cell proliferation, migration, and apoptosis [23]. Many drugs are used to modulate MAPK signaling pathway to induce cell apoptosis in cells, such as lung cancer [40], human colorectal cancer [41], and cervical cancer HeLa cells [42]. Finally, we checked MAPK signaling pathway-related proteins, ERK, p38, and JNK.…”
Section: Discussionmentioning
confidence: 99%
“…3MA and Baf-A1 are often used to inhibit autophagy activation ( 5 ). 3MA inhibits autophagy initiation ( 23 ), and Baf-A1 disturbs the fusion of autophagosomes with lysosomes ( 24 ). The inhibitory effects of 3MA or Baf-A1 on autophagy activation are also decided by their concentrations and treatment times.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory effects of 3MA or Baf-A1 on autophagy activation are also decided by their concentrations and treatment times. Higher concentrations of 3MA or Baf-A1 and longer incubation times lead to obvious changes in the baseline level of autophagy-related proteins ( 23 , 24 ). In the present study, the cells were incubated with 5 mmol/l 3MA and 1.5 µmol/l Baf-A1 for 25 h, which did not exhibit marked inhibition on the baseline levels of autophagy-related proteins ( Fig.…”
Section: Resultsmentioning
confidence: 99%